2017
DOI: 10.1093/jac/dkx281
|View full text |Cite
|
Sign up to set email alerts
|

HIV pretreatment drug resistance trends in three geographic areas of Mexico

Abstract: Our study suggests different NNRTI PDR prevalence and transmission dynamics in three geographical areas of Mexico. Even when increasing trends in efavirenz resistance were observed in the three areas, our observations support that, in a large country such as Mexico, subnational surveillance and locally tailored interventions to address drug resistance may be a reasonable option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In the Mexican context, two nationally representative surveys have shown efavirenz/ nevirapine PDR levels close to 10% [8,9]. In addition, a study by our group demonstrated significant increases in efavirenz/nevirapine PDR levels in different areas of the country from 2008 to 2016, including Mexico City [10]. These results, together with advocacy and stewardship efforts, led to a change in national policy to recommend and procure ART regimens containing second-generation integrase strand-transfer inhibitors (INSTI), mainly bictegravir, as preferred first-line options since 2019 [11].…”
Section: Introductionmentioning
confidence: 54%
“…In the Mexican context, two nationally representative surveys have shown efavirenz/ nevirapine PDR levels close to 10% [8,9]. In addition, a study by our group demonstrated significant increases in efavirenz/nevirapine PDR levels in different areas of the country from 2008 to 2016, including Mexico City [10]. These results, together with advocacy and stewardship efforts, led to a change in national policy to recommend and procure ART regimens containing second-generation integrase strand-transfer inhibitors (INSTI), mainly bictegravir, as preferred first-line options since 2019 [11].…”
Section: Introductionmentioning
confidence: 54%
“…HIVDR testing was performed on specimens with VL ≥1000 copies/mL according to the WHO/HIV ResNet Laboratory Operational Framework . Briefly, HIV protease and reverse transcriptase were amplified from plasma virus, using an in‐house‐validated protocol (HXB2: 2243 to 3304) and sequences were obtained on a 3730xl Genetic Analyser (ThermoFisher, Waltham, MA) . Integrase (IN) was amplified and sequenced separately, using an in‐house‐validated protocol (HXB2: 4013 to 5265) .…”
Section: Methodsmentioning
confidence: 99%
“…Our data set was compiled using all available HIV subtype B partial pol sequences, the predominant circulating subtype in the United States and Mexico [19,20] and samples obtained in convenience based efforts from participants enrolled in (i) the San Diego Primary Infection Resource Consortium (SD PIRC) from 1996 to 2018 and (ii) in Tijuana as part of the Mexican HIV Drug Resistance Surveillance Network studies (76%) [10,21], the Enlaces and El Cuete research studies (24%) [22]…”
Section: Compilation Of Data Sets For Phylogenetic Inferencementioning
confidence: 99%
“…The HIV epidemic in the San Diego-Tijuana border region is complex. In contrast to other parts of Mexico and the United States that have epidemics in which the major risk group are men who have sex with men (MSM), the HIV epidemic along the border is more distributed among risk populations, including MSM, persons who inject drugs (PWID), persons who have transactional sex, and Mexican and Central American migrants [5][6][7][8][9][10]. Hence, the San Diego-Tijuana border region is at the crossroad of multiple risk groups, which leads to transmissions between risk groups [11], possibly enhancing the spread of HIV [12].…”
Section: Introductionmentioning
confidence: 99%